The NIH Toolbox for cognitive surveillance in Duchenne muscular dystrophy. Issue 9 (31st August 2019) - Thangarajh, Mathula; Kaat, Aaron J.; Bibat, Genila; Mansour, Jennifer; Summerton, Katherine; Gioia, Anthony; Berger, Carly; Hardy, Kristina K.; Wagner, Kathryn R.
Abstract: Objective: We performed a prospective, cross‐sectional cognitive assessment in subjects with Duchenne Muscular Dystrophy (DMD) and their biological mothers. Methods: Thirty subjects with out‐of‐frame mutations in the dystrophin ( DMD) gene, and 25 biological mothers were evaluated using the National Institutes of Health Toolbox Cognition Battery (NIHTB‐CB). A parent completed the Behavior Rating Inventory of Executive Functioning (BRIEF), a standardized rating scale of executive functioning, for their child. Mothers completed self‐reports of BRIEF and Neuro Quality‐of‐Life (NeuroQoL) Cognitive Function. Results: Overall, the subjects with DMD scored approximately one standard deviation (SD) below age‐corrected norms on the NIHTB‐CB Total Cognition score. They scored 1.5 SD below age‐corrected norms in Fluid Cognition, which evaluates the cognitive domains of executive function, working memory, episodic memory, attention, and processing speed. Their performance was consistent with age expectations (i.e., within 1 SD below age‐corrected norms) in Crystalized Cognition, which evaluates vocabulary and reading. Subjects with DMD had higher T‐scores in several domains of BRIEF, demonstrating greater difficulty in executive functioning. The biological mothers had overall average or above average T‐scores on NIHTB‐CB. Mothers who were carriers of DMD mutation performed lower overall compared to mothers who were not carriers of DMD mutation (Cohen's d  = −1.1). Carrier mothers performed lower than average (1.5 SD) in Executive Function, measured by Flanker Inhibitory Control and Attention. Biological mothers scored within expected score ranges for adults in BRIEF and NeuroQoL. Interpretation: The NIHTB‐CB, combined with standardized self‐reported measures, can be a sensitive screening tool for cognitive surveillance in DMD.